Profile of collagen prolines level of anterior rectus sheath tissue in indirect inguinal hernia: A cross-sectional study. (August 2021) - darmadi, Suluh; Warsinggih,; Mappincara,; Hendarto, Joko; Labeda, Ibrahim; Lusikooy, Ronald Erasio; Sampetoding, Samuel; Dani, Muhammad Iwan; Kusuma, Muhammad Ihwan; Uwuratuw, Julianus Aboyaman; Syarifuddin, Erwin; Faruk, Muhammad
Abstract: Introduction: A hernia is a protrusion of an organ or tissue through an abnormal anatomical channel or opening. Epidemiological data indicated an increased prevalence of inguinal hernias in patients with connective tissue diseases. The biomechanical strength of connective tissue is highly dependent on the constituent of the matrix, including collagen. Fibroblasts produce and secrete procollagen containing high concentrations of proline and lysine. Collagen integrity plays an essential role in preventing hernia formation in the abdominal wall. To investigate the relationship between collagen proline levels of the anterior rectus sheath tissue in patients with lateral inguinal hernias (indirect inguinal hernia). Methods: The study participants consisted of 67 inguinal hernia patients. A sample of anterior rectus tissue was obtained at the time of surgery, then being washed in a PBS buffer (pH 7.4). The measurement of collagen proline levels was subsequently carried out with enzyme linked immunosorbent assay (ELISA). Results: All study participants were male with mean age of 44 years, mean body mass index of 22.6 kg/m 2 and mean onset of events of 27 months. Study subjects with reducible, irreducible, and incarcerated hernias were 45.7% (44/67 cases), 14.9% (10/67) and 19.4% (13/67), respectively. The mean proline level of the study subjects was 9.20. Correlation tests showed a correlation of proline levels and age (p = 0.001), body mass index (p = 0.006), and the onset of events (p = 0.023). Meanwhile, correlation of proline levels and occupation (p = 0.235) and clinical degree (p = 0.164) were not statistically significant. Conclusion: Presence if relationship between proline levels with age, and onset of incidence among indirect inguinal hernia patients. HIGHLIGHT: Collagen is the main structural protein in the muscle wall layer. Defects in collagenases will result in abnormal collagen synthesis leading to pathological collagen degradation. Decreases in hydroxyproline and collagen were observed in the fascia and muscle tissue of patients with inguinal hernias. There are a relationship between proline levels with age, and onset of incidence among indirect inguinal hernia.